Study on Cost Analysis and Time Acceleration With CPM Method And Earned Value Method at Madegan Market Renovation Work of Ponorogo Regency - Harry Susanto (Wacana Journal of Social and Humanity Studies, 2019)
Cost and time deviation gives indication that construction project management is poor. In the reality shows that project completion time varies, as result the estimated time of project completion cannot be ensured. The research objectives include (1) Obtaining estimation of time needed to complete the renovation work, (2) Obtaining estimation  of final project cost to the work contract value for renovating, (3) Gaining profit or loss in doing the work renovation of Badegan Market. The research method used CPM and Earned Value methods. The results showed that (1) Using the Earned Value method, the work performance of market renovation project was as expected and reached the work target and experienced acceleration, the estimated time of project completion was 79.09 days. By using the critical path determination to the CPM, the time it takes to complete the renovation project was 80 days, can be accelerated 40 days from initial planning 120 days, (2) The estimated cost of renovation project was equal to the contract value, amounting to IDR 3,673 Billion, (3) Based on the Cost Variance value, in the Market Renovation project, the contractor earns profit or costs incurred by the contractor less than the available budget of IDR 283,494 Million.